The Effect Of Extra And Intra-Campus Organizational Communications On Public Speaking Ability Among Students Of The Faculty Of Social Sciences UINSU (Pena Cendekia Insani, 2022)
This study aims to determine how the influence of organizational communication in extra and intra-campus on students' public speaking skills . The research was conducted using quantitative research methods . The population used were students of the 2018 Stambuk Communication Science Department as many as 361 people at the State Islamic University of North Sumatra (UINSU) Medan , and using a purposive sampling technique , with the slovin formula with an error rate of 10% and the sample being studied was 79 respondents. through the distribution of questionnaires. The results of this study on the t test stated that organizational communication has a t count> T table (97.34 > 1.99125) with a significance level (0.05), then H0 is Rejected and Ha Accepted, meaning that communication extra and intra-campus organization affect the ability of public speaking students.